Improving Girls' Sense of Fit in Science: Increasing the Impact of Role Models. (April 2017) - O'Brien, Laurie T.; Hitti, Aline; Shaffer, Emily; Camp, Amanda R. Van; Henry, Donata; Gilbert, Patricia N.
A field experiment tested the effect of choosing a "favorite" role model on sense of fit in science among middle school girls. The girls participated in a 1-day science outreach event where they were exposed to multiple female role models. At the end of the event, participants were randomly assigned to choose and write about a favorite role model or to choose and write about their best friend. Girls in the role model choice condition experienced a significant increase in sense of fit in science, whereas girls in the control condition did not. Girls in the role model choice condition also tended to have stronger role model identification than girls in the control condition, and role model identification was correlated with sense of fit in science. Encouraging girls to actively choose and write about a favorite role model may help to maximize the impact of exposure to role models.